Allelopathic potential of aqueous extracts from Tithonia diversifolia (Hemsl.) A. Gray - Henzel, Ana Beatriz Devantier; Moreira da Luz Real, Isadora; Guarino, Ernestino Souza Gomes; Schiedeck, Gustavo; Mauch, Carlos Rogério (Scientia Agraria Paranaensis, 2022)
Tithonia diversifolia (Hemsl.) A. Gray has been recommended as a fertilizer species and its liquid extract as a biofertilizer in organic agroforestry systems. However, studies indicate that plant extracts have inhibitory effects on the germination and growth of several plant species, acting as allelopathic. In this sense, the work aims to evaluate, on a laboratory scale, the biological effect of concentrations of aqueous extract of T. diversifolia on the germination and initial development of seeds, using lettuce as an indicator species. Aqueous extracts were produced at concentrations of 5%, 10%, 15%, and 20%, using distilled water as a control. Lettuce seeds were arranged in Gerbox boxes, on filter paper, in the amount of 25 seeds per box, under a constant temperature of 20°C and natural light, for seven days. The percentage of final germination, mean germination time (MGT), germination speed index (GSI), and phytosanitary status of the seed on the seventh day were evaluated. The aqueous extracts of T. diversifolia in concentrations between 5% and 20% do not affect the final germination of the seeds, however, they reduce the germination speed; affect seedling size, and induce a higher percentage of abnormalities in germinated seeds. The results suggest that extracts of T. diversifolia have allelopathic potential for the germination of species.